TINJAUAN TENTANG BUDAYA ISLAM DI TANAH JAWA BERDASARKAN DALIL-DALIL PEMAHAMAN IMAM SYAFIâI - Syarifuddin, Amir; Mustafa, Muhammad Hatta (Fakultas Hukum Universitas Sebelas Maret, 2014)
ABSTRACTThe Islamic tradition which becom the part of islamic life in our Countri, especiallyÂ inÂ JavaÂ island,Â ratherÂ hadÂ shake-up,Â thisÂ problemÂ causedÂ byÂ the enternity of the other culture to Indonesia that influence the understanding to each others. The reality insociety shows that islamic tradition which is maintained can limit the negatif effecct of foreign culture which entered, especially western. The reflectionÂ ofÂ YasinÂ andÂ othersÂ epistleÂ inÂ AlÂ QurâanÂ andÂ tahlil,Â tasbih,Â tahmid, shalawat andÂ other dzikir is a part that can be separated from islamic culture and javaÂ culture.Â AllÂ ofÂ themÂ isÂ reflectedÂ fromÂ societyÂ thatÂ stillÂ combineÂ between cultureÂ andÂ religion,Â itÂ canÂ beÂ understoodÂ fromÂ ruwahÂ culture(ngirim arwah)/ziarah,Â yassinanÂ culture,Â dzikirÂ culture,Â andÂ others.Â ItÂ isÂ canÂ notÂ be separatedÂ fromÂ islamicÂ daâwahÂ thatÂ spreadÂ byÂ waliÂ songoÂ thatÂ acculturatedÂ the culture, so it is easy to be understood by the society especially Java society.